Mathematical Connection Ability in REACT Learning with RME Approach in Term of Self-efficacy - Ainurrachmani, Fitrania; Safa'atullah, Muh. Fajar (Department of Mathematics, Universitas Negeri Semarang, 2022)
Mathematical connection ability is one of the important abilities. The students' self-efficacy also needs to be considered. The purpose of this study was to determine the students' mathematical connection ability in REACT learning with the RME approach in terms of students' self-efficacy. This research uses mix method with a sequential explanatory design. The population in this study were eighth-grade students of Integrated Islamic Junior High School Nurul Islam Tengaran. The research instrument used was a test of mathematical connection ability and a self-efficacy questionnaire. The results of this study are (1) the mathematical connection ability of students with REACT learning using the RME approach achieves the criteria for learning mastery; (2) the average mathematical connection ability of students with REACT learning using the RME approach was better than students with expository learning; (3) there are differences in students' mathematical connection abilities in terms of students' self-efficacy levels in REACT learning with the RME approach; (4) Students with high self-efficacy fulfill the three indicators of mathematical connection ability. Students with medium self-efficacy are sufficient to meet the three indicators of mathematical connection ability but still need more practice. Students with low self-efficacy only fulfilled the second mathematical connection ability indicator.